IMPLEMENTASI KEBIJAKAN PERATURAN PELAYANAN MANAJEMEN KEPENSIUNAN Tinjauan Implementasi Peraturan Direksi Nomor PD- 12/DIR/2012 PT.TASPEN (Persero) Denpasar - Natalia, Anak Agung Ayu Primayuni; Erviantono, Tedi; Winaya, I Ketut (CITIZEN CHARTER, 2015)
ABSTRACT Regulation of the Board of Directors Number: PD-12/DIR/2012  servers regulations used by PT. TASPEN  (Persero)  as guidelines  for the implementation  of main duties and their functions to manage   Pension   Program   including   Retirement   Saving   Program,   and   Participant   Data Management  to Retired  Civil Servants.  Regulation  of the Board  of Directors  is also used to recommend   the  success  and  failure  of  service  regulations  established   by  PT.  TASPEN (Persero) related to post-retirement reforms (pensions). This study used a qualitative descriptive method. With the interactive model analysis by Milles and Huberman (1992), which consists of three  components  of analysis,  namely  the analysis  of data reduction,  data presentation  and drawing  of a conclusion.  The  writer  conducted  direct  interviews  and  observation  by looking directly   at  the  phenomena   that  occured   in  the  field.  The  results   of  the  study   is  the implementation of program services and superannuation pension run by PT. TASPEN (Persero) Branch  of Denpasar  has been going well and in accordance  with the policies  set out in the Directors  Rule Number:  PD-12/DIR/2012.  However,  implementation  has encountered  several obstacles that hindered the implementation of services to participants such as pension file management and participant data management. The role TASPEN in providing solutions related to constraints  that occur is through some form of socialization  strategies  that direct services, socialization  with the use of electronic  and printed media, external and internal reconciliation routine  as  well  as  financial  reconciliation  and  ease  of  service  benefit  from  their  services customers visits, e-banking, MOBTAS services, and 1 hour services.   Keywords: Policy Implementation  of Service Regulations, Retirement Management,  Regulation of the Board of Directors Number: PD-12/DIR/2012 PT. TASPEN (Persero)IMPLEMENTASI KEBIJAKAN PERATURAN PELAYANAN MANAJEMEN KEPENSIUNAN Tinjauan Implementasi Peraturan Direksi Nomor PD- 12/DIR/2012 PT.TASPEN (Persero) Denpasar